2015
DOI: 10.1371/journal.pone.0123549
|View full text |Cite
|
Sign up to set email alerts
|

Malarial Anaemia and Anaemia Severity in Apparently Healthy Primary School Children in Urban and Rural Settings in the Mount Cameroon Area: Cross Sectional Survey

Abstract: BackgroundThis study examines the relative importance of living in an urban versus rural setting and malaria in contributing to the public health problem of malarial anaemia (MA) and anaemia respectively in apparently healthy primary school children.MethodsA cross-sectional study was conducted among 727 school children aged between four and 15 years living in an urban (302) and rural (425) settings in the Mount Cameroon area. Blood sample collected from each child was used for the preparation of blood films fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 43 publications
6
52
3
1
Order By: Relevance
“…Why females had a higher attributable risk of anaemia and moderate to severe anaemia due to malaria is unclear as no significant gender differences were observed in prevalence and density. Even though studies on the attributable risk of anaemia and moderate to severe anaemia due to falciparum malaria have seldom been carried out in Cameroon, previous studies in the Mount Cameroon area, in apparently healthy children, revealed a moderate (24.5%) contribution of falciparum malaria to anaemia [23]. Inferences from both studies most likely indicate the notion that of greater importance is the contribution of asymptomatic P. falciparum infection to the public health problem of anaemia compared to falciparum infection in febrile children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why females had a higher attributable risk of anaemia and moderate to severe anaemia due to malaria is unclear as no significant gender differences were observed in prevalence and density. Even though studies on the attributable risk of anaemia and moderate to severe anaemia due to falciparum malaria have seldom been carried out in Cameroon, previous studies in the Mount Cameroon area, in apparently healthy children, revealed a moderate (24.5%) contribution of falciparum malaria to anaemia [23]. Inferences from both studies most likely indicate the notion that of greater importance is the contribution of asymptomatic P. falciparum infection to the public health problem of anaemia compared to falciparum infection in febrile children.…”
Section: Discussionmentioning
confidence: 99%
“…The socioeconomic status was classified as poor, average, and rich as described by Kimbi et al [5] and Sumbele et al [23]. …”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the prevalence of malaria among the study participants was 98.5 %, which is very high compared to the prevalence reported in children in other areas of the Southwest Region of Cameroon. This includes the 50.7 % reported in villages in Mbonge [ 11 ], 33.8 % in Limbe and Buea [ 28 ], and 40.6 % in the Centre Region of Cameroon [ 29 ]. These discrepancies could be explained by the fact that the present study was hospital-based in which febrile children were enrolled, compared to the other studies in which apparently healthy children either from schools or the community were enrolled.…”
Section: Discussionmentioning
confidence: 99%
“… Fever was considered as armpit temperature ≥ 37.5°C [21].  Asymptomatic malaria was defined as the presence of malaria parasite with an axillary temperature < 37.5°C [22].…”
Section: Operational Definitionsmentioning
confidence: 99%